The Role of Intelligence in Man-Made Disasters that Trigger Social Conflict in Indonesia - Alif Fadzilatus Siti Arofah; Eko G Samudro; Yulian Azhari; Arifuddin Uksan; Pujo Widodo (Formosa Journal of Social Sciences (FJSS), 2024)
Disasters caused by human activities are among the factors that can cause social conflict in Indonesia. At this moment, intelligence plays a role in dealing with these artificial disasters so that they can de-escalate the conflict. This research is in the form of a descriptive qualitative literature study. Data sources were obtained from scientific articles, books, and relevant news articles. The research results show several types of social conflict in Indonesia, including ethnicity, race, religion and class, and political conflict. Intelligence plays a role in gathering sharp information. This information must be processed behind closed doors, interpreted by the intelligence team, and then submitted to the leadership to determine the appropriate steps